Vitamin D Metabolism Varies among Women in Different Reproductive States Consuming the Same Intakes of Vitamin D and Related Nutrients. Issue 8 (22nd June 2016) - Park, Heyjun; Brannon, Patsy M; West, Allyson A; Yan, Jian; Jiang, Xinyin; Perry, Cydne A; Malysheva, Olga V; Mehta, Saurabh; Caudill, Marie A
Abstract: Background: The impact of the reproductive state on vitamin D metabolism and requirements is uncertain in part because of a lack of studies with controlled dietary intakes of vitamin D and related nutrients. Objective: We aimed to quantify the impact of the reproductive state on a panel of vitamin D biomarkers among women of childbearing age consuming equivalent amounts of vitamin D and related nutrients. Methods: Nested within a feeding study providing 2 doses of choline, healthy pregnant (26–29 wk gestation; n = 26), lactating (5 wk postpartum; n = 28), and control (nonpregnant/nonlactating; n = 21) women consumed a single amount of vitamin D (511 ± 48 IU/d: 311 ± 48 IU/d from diet and 200 IU/d as supplemental cholecalciferol) and related nutrients (1.6 ± 0.4 g Ca/d and 1.9 ± 0.3 g P/d) for 10 wk. Vitamin D biomarkers were measured in blood obtained at baseline and study end, and differences in biomarker response among the reproductive groups were assessed with linear mixed models adjusted for influential covariates (e.g., body mass index, season, race/ethnicity). Results: At study end, pregnant women had higher ( P < 0.01) circulating concentrations of 25-hydroxyvitamin D [25(OH)D; 30%], 1, 25-dihydroxyvitamin D [1, 25(OH)2 D; 80%], vitamin D binding protein (67%), and C3 epimer of 25(OH)D3 (100%) than control women. Pregnant women also had higher ( P ≤ 0.04) ratios of 25(OH)D to 24, 25-dihydroxyvitamin D [24, 25(OH)2 D; 40%] and 1, 25(OH)2 D to 25(OH)D (50%) than control women. In contrast, no differences ( P ≥ 0.15) in vitamin D biomarkers were detected between the lactating and control groups. Notably, the study vitamin D dose of 511 IU/d achieved vitamin D adequacy in most participants (95%) regardless of their reproductive state. Conclusions: The higher concentrations of vitamin D biomarkers among pregnant women than among control women suggest that metabolic adaptations, likely involving the placenta, transpire to enhance vitamin D supply during pregnancy. The study findings also support the adequacy of the current vitamin D RDA of 600 IU for achieving serum 25(OH)D concentrations ≥50 nmol/L among women differing in their reproductive state. This trial was registered at clinicaltrials.gov as NCT01127022.